Perancangan Sistem Pelaporan Harian Menggunakan Metode SDLC Pada Stasiun Pengumpul Minyak dan Stasiun Kompresor Gas - Ainna Khansa; Billan, Angel Caroline; Tata Sutabri (Bulletin of Computer Science Research, 2024)
Current information delivery can be delivered through a system adopted by the company to assist in the company's performance process. One of the systems needed by the company is a reporting system that is used as an effective channel for delivering company data information results. The problem that occurs is that many company employee performance processes are considered inefficient in carrying out the reporting process. Company reporting using Hand Talky (HT) and Radio Link, is considered vulnerable to inaccuracy between data and communication barriers. To adopt a system technology in a large-scale company, of course the system must be easy for users to use and the process is fast. The solution produced for this problem is to design a daily reporting system using the SDLC (System Development Life Cycle) method. This design aims to apply the SDLC (System Development Life Cycle) method to the design of a system that can provide information remotely, provide real-time data updates, and present data in a more structured format for data management. This system is designed to automate the data backup process to reduce manual intervention in company data security. The proposed system is expected to increase the efficiency of operational activities in achieving company targets and improve overall performance in the company's data reporting process. The use of the SDLC method approach by researchers in designing a reporting system has been proven to accelerate system design. The results of the study showed that the design of this system was able to reduce reporting time by 50%, increase data accuracy by 40%, and provide significant user satisfaction.